Environmental law - Sengar, Dharmendra S. (New Delhi : Prentice Hall of India Learning, 2007)
With reference to India
Book is accompanied by 1 computer optical disc, entittle'environmental Law' bearing the same call number and is available at Bahagian Koleksi Media
Includes index
Keywords: Environmental law -- India